Gitanjali (Song-offerings) - CARPENTER, John Alden (G. Schirmer. Inc., 1914)
When i bring to you colour'd toysnOn the day when death will knock at thy doornThe sleep that on baby's eyesnI am like a remnant of a cloud of autumnnOn the seashore of endless worlds